Cellulase-Hemicellulase Activities and Bacterial Community Composition of Different Soils from Algerian Ecosystems - Houfani, Aicha Asma; Větrovský, Tomáš; Navarrete, Oscar U; Štursová, Martina; Tláskal, Vojtěch; Beiko, Robert G; Boucherba, Nawel; Baldrian, Petr; Benallaoua, Said; Jorquera, Milko A (Microbial ecology, 2019)
Soil microorganisms are important mediators of carbon cycling in nature. Although cellulose- and hemicellulose-degrading bacteria have been isolated from Algerian ecosystems, the information on the composition of soil bacterial communities and thus the potential of their members to decompose plant residues is still limited. The objective of the present study was to describe and compare the bacterial community composition in Algerian soils (crop, forest, garden, and desert) and the activity of cellulose- and hemicellulose-degrading enzymes. Bacterial communities were characterized by high-throughput 16S amplicon sequencing followed by the in silico prediction of their functional potential. The highest lignocellulolytic activity was recorded in forest and garden soils whereas activities in the agricultural and desert soils were typically low. The bacterial phyla Proteobacteria (in particular classes α-proteobacteria, δ-proteobacteria, and γ-proteobacteria), Firmicutes, and Actinobacteria dominated in all soils. Forest and garden soils exhibited higher diversity than agricultural and desert soils. Endocellulase activity was elevated in forest and garden soils. In silico analysis predicted higher share of genes assigned to general metabolism in forest and garden soils compared with agricultural and arid soils, particularly in carbohydrate metabolism. The highest potential of lignocellulose decomposition was predicted for forest soils, which is in agreement with the highest activity of corresponding enzymes.
Keywords: Forests; glykosidhydrolasy; Glycoside Hydrolases; lesy; bakteriální proteiny; Bacterial Proteins; Cellulase; Alžírsko; Algeria; půdní mikrobiologie; Phylogeny; celulasa; Bacteria; Soil Microbiology; ekosystém; Ecosystem; Soil; půda; fylogeneze